2002
DOI: 10.1002/bem.10043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a time varying strong magnetic field on release of cytosolic free Ca2+ from intracellular stores in cultured bovine adrenal chromaffin cells

Abstract: This study was made to explain the mechanisms for the effects of exposure to a time varying 1.51 T magnetic field on the intracellular Ca(2+) signaling pathway. The exposure inhibited an increase in intracellular Ca(2+) concentration ([Ca(2+)](i)) in bovine chromaffin cells induced by addition of bradykinin (BK) to a Ca(2+) free medium. The exposure did not change BK induced production of inositol 1,4,5-trisphosphate (IP(3)). [Ca(2+)](i) was markedly increased in IP(3) loaded cells, and this increase was inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Pulsed electromagnetic fields (PEMFs) are capable in altering the structure of the cell membranes and thus diversify the permeability of different ion channels and the potential of the cellular membranes. Both phenomena are important of cellular functions [Blackman et al, 1980;Walleczek and Liburdy, 1990;Ikehara et al, 2002], such as the production of chemical energy in the form of adenosine triphosphate (ATP) and the variance of intracellular free calcium levels, which is a second type universal intermediate ion [Carafoli, 2004]. They may also conserve the normal electrochemical gradient of cells, a necessary condition for ATP production, which may be lowered by ischemia or trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed electromagnetic fields (PEMFs) are capable in altering the structure of the cell membranes and thus diversify the permeability of different ion channels and the potential of the cellular membranes. Both phenomena are important of cellular functions [Blackman et al, 1980;Walleczek and Liburdy, 1990;Ikehara et al, 2002], such as the production of chemical energy in the form of adenosine triphosphate (ATP) and the variance of intracellular free calcium levels, which is a second type universal intermediate ion [Carafoli, 2004]. They may also conserve the normal electrochemical gradient of cells, a necessary condition for ATP production, which may be lowered by ischemia or trauma.…”
Section: Introductionmentioning
confidence: 99%
“…EMFs may increase intracellular Ca 2? concentrations in various types of cells [22,23] inducing thus apoptosis also on prostate cancer cells [24]. Radiofrequency fields have been shown to exert apoptotic effects on malignant cell lines [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Study revealed that Calcium-ion could adjust many species physiology actions as one of the second messenger, it also take part in regulation of proliferation, excretion and migration of the cells after exposure on the magnetic field [3]. There were reports that the concentration of the intracellular Calcium-ion or the calcium-signal increased after the exposure of the magnetic field [4], [5], on the contrary, other reports suggest that the concentration of the intracellular Calcium-ion or the calcium-signal decreased after the exposure of the magnetic field [6], [7], some reports suggest that magnetic field have no effects on the concentration of the Calcium-ion [8], [9]. All of the above reports showed that the effects of magnetic field on the concentration of intracellular Calcium-ion were complicated, it has relation to the frequency and the intensity of the magnetic field, the time exposure on the magnetic field and the type of the cells.…”
Section: Discussionmentioning
confidence: 99%